Cardiovascular Disease Risk Factors Among Mining Workers at PT. Manggala Alam Lestari - Jansen Fernando; Oktavia Dewi; Mitra Mitra; Jasrida Yuita; Agus Alamsyah; Musfardi Rustam (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
This study aimed to analyze the risk factors associated with cardiovascular disease (CVD) among mining workers at PT Manggala Alam Lestari, Musi Banyuasin, South Sumatra, Indonesia. A retrospective case-control study was conducted using secondary data from routine Medical Check-Up (MCU) records collected between 2022 and 2024. A total of 400 workers were included, comprising 80 CVD cases and 320 controls selected using a 1:4 frequency matching strategy by age group (≤45 and >45 years) and gender. Data analysis involved univariate summaries, bivariate chi-square tests, and multivariate multiple logistic regression to obtain adjusted odds ratios (aOR) and 95% confidence intervals while controlling for potential confounders, including age, gender, and work shift. Five significant modifiable risk factors were identified: obesity, diabetes mellitus, hypertension, dyslipidemia, and smoking. Obesity showed the strongest association with CVD (aOR ≈ 9.4), followed by diabetes mellitus (aOR ≈ 8.4), hypertension (aOR ≈ 7.6), dyslipidemia (aOR ≈ 5.2), and smoking (aOR ≈ 4.0). The final logistic regression model demonstrated good performance, with a Nagelkerke R² value of 0.645, indicating that 64.5% of the variation in CVD status could be explained by these five factors, and acceptable model fit on diagnostic testing. In conclusion, obesity and other metabolic and behavioral factors are strongly associated with CVD among mining workers at this site. Targeted occupational health interventions focusing on weight management, early detection and control of metabolic disorders, and comprehensive smoking cessation programs are essential to reduce the burden of CVD in the mining industry Keywords: Cardiovascular Disease, Mining Industry, Metabolic Risk Factors, Obesity, Occupational Health